Vacuum enclosures for solar thermal panels Part 2: Transient testing with an uncooled absorber plate. (1st November 2018) - Arya, Farid; Moss, Roger; Hyde, Trevor; Shire, Stan; Henshall, Paul; Eames, Philip
Highlights: Vacuum Flat Plate Collectors fabricated involving Ultrasonic Soldering techniques. Heat transfer from/to a copper plate in a vacuum enclosure theoretically calculated. Enclosures tested under a solar simulator and stagnation temperatures were determined. Estimation of Absorbance, Emissivity and Gas Conductivity calculated. The enclosure and copper plate were modelled as if the plate were water-cooled. Abstract: Creating a vacuum (<1 Pa) around a solar absorber in a flat plate solar thermal collector can increase efficiency by minimising gaseous conduction and convection between the absorber plate and the glass cover. High performance and architecturally attractive flat plate solar thermal collectors are appealing to building owners and designers for supplying clean and renewable energy cost effectively produced via the façade of the building. This two part paper describes the construction techniques and thermal performance of two vacuum enclosures, fabricated at Ulster University, as prototype components for evacuated flat plate solar collectors. The enclosures were tested at three conditions: 0.0033 Pa, 17 Pa and atmospheric pressure. The first enclosure consisted of two glass panes, sealed to an edge spacer and separated by an array of support pillars on a regular square grid to form a narrow evacuated space. The second enclosure, incorporated an uncooled copper plate to represent a solar thermal absorber. Part 1 of this paper has described the fabrication techniques and compared results from hot-box calorimeter and IR thermography testing of the first enclosure with numerical and analytical predictions. Part 2 describes solar simulator testing of the second enclosure which incorporated an uncooled copper plate. Testing under a solar simulator showed a higher stagnation temperature in the high vacuum test (0.0033 Pa) in comparison with the low vacuum (17 Pa) and atmospheric pressure tests. Curve fitting of a heat transfer model to the transient response data demonstrated that radiation and gas conduction were close to predictions. Simulated results were in close agreement with both the transient response and the steady-state asymptotic plate temperatures.